2013
DOI: 10.3390/molecules19010159
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of CUL4A in Regulation of Multidrug Resistance to P-gp Substrate Drugs in Breast Cancer Cells

Abstract: CUL4A encodes a core component of a cullin-based E3 ubiquitin ligase complex that regulates many critical processes such as cell cycle progression, DNA replication, DNA repair and chromatin remodeling by targeting a variety of proteins for ubiquitination and degradation. In the research described in this report we aimed to clarify whether CUL4A participates in multiple drug resistance (MDR) in breast cancer cells. We first transfected vectors carrying CUL4A and specific shCUL4A into breast cancer cells and cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…The generation of retrovirus supernatants and the transfection of cells were conducted as described in a previous study (18). Infected cells were selected by the addition of 2 μg/ml puromycin (Sigma, St. Louis, MO, USA) to the culture medium for 48 h and then maintained in complete medium with 1 μg/ml puromycin.…”
Section: Methodsmentioning
confidence: 99%
“…The generation of retrovirus supernatants and the transfection of cells were conducted as described in a previous study (18). Infected cells were selected by the addition of 2 μg/ml puromycin (Sigma, St. Louis, MO, USA) to the culture medium for 48 h and then maintained in complete medium with 1 μg/ml puromycin.…”
Section: Methodsmentioning
confidence: 99%
“…Histone H3K27 methyltransferase, EZH2, and H3K4 demethylases LSD1 and KDM5B have been thought to play important roles not only in tumor initiation, but also in tumor progression, since overexpression of these genes has been reported in many types of malignant tumors [30]. Previous papers revealed that upregulation of KDM5B enhanced cell migration, cell invasion and EMT to promote malignant progression of lung cancer cells [32,33]. However, the role of KDM5B in glioma carcinogenesis remains unclear.…”
Section: Discussionmentioning
confidence: 96%
“…20,21 Genetic studies have shown that c-MYC proto-oncogene encodes a transcription factor, MYC, which is a central regulator of cell growth, proliferation, and apoptosis. 13,12 Enhanced levels of MYC are thought to contribute to the formation of many human tumors.…”
Section: Discussionmentioning
confidence: 99%